DISPARITAS PENDAPATAN, KEMISKINAN DNA KETAHANAN PANGAN MASYARAKAT TRANSMIGRAN DI KECAMATAN TANJUNG SELOR, BULUNGAN - Karolus Sonu; Irham Irham; Jamhari Jamhari (Agro Ekonomi, 2011)
The objective of the study is to understand disparity rate of income, poverty category, and food sustainability within transmigration community. This study was taken infzve residential units of transmigration in Tanjung Selor subdistrict, with 80 households as respondents. The result suggests that income distribution within transmigration society is evenly distributed (Gini Coefficient